2022
DOI: 10.1038/s41386-022-01306-4
|View full text |Cite
|
Sign up to set email alerts
|

In vivo imaging translocator protein (TSPO) in autism spectrum disorder

Abstract: Converging evidence points to the significant involvement of the immune system in autism spectrum disorders (ASD). Positron emission tomography (PET) can quantify translocator protein 18 kDa (TSPO), a marker with increased expression mainly in microglia and, to some extent astroglia during neuropsychiatric diseases with inflammation. This preliminary analysis explored, for the first time, whether TSPO binding was altered in male and female participants with ASD in vivo using full kinetic quantification. Thirte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 80 publications
1
14
0
Order By: Relevance
“…In addition, the 18 kDa translocator protein (TSPO) is highly responsive to inflammatory stimulation, which seemed as an in vivo marker of microglia activation ( 48 , 49 ). Recent studies have sought to detect activated microglia in patients using positron emission tomography for the TSPO ( 48 ), and shreds of evidence suggested TSPO was broadly increased in different brain regions of ASD, including pre-frontal, temporal, cerebellar, and anterior cingulate cortices ( 50 ).…”
Section: The Regulation Of Microglia On Inflammationmentioning
confidence: 99%
“…In addition, the 18 kDa translocator protein (TSPO) is highly responsive to inflammatory stimulation, which seemed as an in vivo marker of microglia activation ( 48 , 49 ). Recent studies have sought to detect activated microglia in patients using positron emission tomography for the TSPO ( 48 ), and shreds of evidence suggested TSPO was broadly increased in different brain regions of ASD, including pre-frontal, temporal, cerebellar, and anterior cingulate cortices ( 50 ).…”
Section: The Regulation Of Microglia On Inflammationmentioning
confidence: 99%
“…Another study has also reported similar findings using [18F]FEPPA, a specific ligand for TSPO to investigate neuroinflammation in ASD patients. The study reported a significant lower [18F]FEPPA total volume of distribution in ASD patients when compared to the control (p = 0.02) [60].…”
Section: Neuroinflammation In Asdmentioning
confidence: 70%
“…Brain tissues obtained from autopsy Neuroinflammation observed in cerebral cortex and white matter, and cerebellum of ASD patients by immunocytochemical methods and cytokine profiling [56] CSF of living ASD patients Cytokine profiling showed neuroinflammation [56] Brain tissues from the dorsolateral prefrontal cortex of ASD individuals Microglia activation reported in individuals as young as < 6 years of age with morphological changes in microglia [57] PET scans using brain microglia radiotracer Findings suggest an increased microglia activation in multiple regions of the brain of subjects with ASD [58] PET scan for TSPO Lower expression of TSPO in several brain regions of patients with ASD when compared with control [59] MR-PET scan of [18F]FEPPA (specific ligand for TSPO) Significantly lower [18F]FEPPA total volume of distribution in ASD patients when compared to the control [60] Brain tissues/blood hormone level of mice Mice showed increased blood cortisone levels, increased microglia in hippocampus and increased proinflammatory cytokines in cerebellum when compared with control group [61] Brain of MIA mice and offspring of MIA mice MIA in pregnant mice led to abnormal cortical development in offspring and increased IL-17a mRNA expression in foetal brain mediated via maternal IL-17a pathway [62] Serum, plasma, CSF and brain of patients with ASD Increased levels of proinflammatory substances like interleukins, chemokines and osteopontin, TNF-α, IF-γ and growth factors [63] Page 8 of 13 Wong Egypt J Neurol Psychiatry Neurosurg (2022) 58:91…”
Section: Source Of Evidence Key Findings Referencesmentioning
confidence: 99%
“…Translocator protein 18 kDa (TSPO), a mitochondrial protein which has neuroimmune functions [ 14 ], has previously been investigated in ASD [ 15 17 ]. Using positron emission tomography–magnetic resonance imaging (PET–MRI), we observed lower regional TSPO relative to the whole brain measured by standardized uptake value ratio (SUVR) in adult males with ASD ( N = 15) compared to age-matched male controls [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Using positron emission tomography–magnetic resonance imaging (PET–MRI), we observed lower regional TSPO relative to the whole brain measured by standardized uptake value ratio (SUVR) in adult males with ASD ( N = 15) compared to age-matched male controls [ 15 ]. Translocator protein levels were also assessed by another research group with [ 18 F]FEPPA PET in a combined group of adult males and females with ASD, revealing either unchanged ( N = 13, males = 8, females = 5) or lower (a subset of N = 11) TSPO levels in the brain using arterial blood-based PET quantification [ 17 ]. Another study which used the cerebellum of the controls as a reference region and the radiotracer [ 11 C]PK11195, which has a lower ratio of specific to nonspecific binding than [ 11 C]PBR28 [ 18 ], reported higher TSPO levels in males with ASD [ 17 ].…”
Section: Introductionmentioning
confidence: 99%